O bicameralismo no Brasil: as bases institucionais e políticas do desempenho legislativo do Senado Federal (1989-2004). - Paulo Magalhaes Araujo (2009)
This work is a study of the legislative process and the production of laws in the Brazilian Senate, relating to the bills that deflagrate the legislative processes in this chamber between 1989 and 2004. The central objective of the study was to analyze the legislative performance of the Senate, in light of their place in a symmetrical and incongruentbicameralism, which is part of a coalitional presidencialism. The general hypothesis that guided the analysis was that the Senate is not an instance of unconditional veto or ratification of projects that appreciates. Being occupied by rational actors, interested to maximize the political and electoral benefits, the propensity of the senators to cooperate orcompete with other decision makers is conditioned by the incentives generated by institutional context in particular the partisan configuration of legislative houses. The research found that the senators make effective the formal symmetry of the bicameralism, showing notorious willingness to legislate, either as beginners or as reviewers of proposalsin process. One of the signs of that political vigour is the fact that the projects of the government under which dealt unilateral urgency of Executive branch has three times more likely to be amended than those conducted in the ordinary process. This shows that the agenda power of the Executive is not enough for him to impose his will. The senators,when necessary, they make use of their political power to assert their interests in front of the other lawmakers. Regarding the issue of bicameral incongruence, the analysis of the political composition of the Brazilian Senate revealed two important phenomena: on the one hand, it was observed that the Senate is, generally, a more favorable environment for agreements that the Chamber of Deputies, to be less fragmented in partisan terms and more moderate in ideological terms; on the other hand, the results found that the legislative performance of senators reflects the institutional structure of the political system, but itsdisposal to intervene in the legislative process is affected by longitudinal variation in the bicameral representation. Statistical tests proved that variations in the size of the coalition, the effective number of parties and the ideological incongruence in the bicameral representation are significantly associated with the propensity of the Senate to amend ornot the bills under review.